Accidental poisoning with Aconitum: Case report and review of the literature. Issue 4 (5th February 2020) - Bonanno, Giuseppe; Ippolito, Mariachiara; Moscarelli, Alessandra; Misseri, Giovanni; Caradonna, Rosaria; Accurso, Giuseppe; Cortegiani, Andrea; Giarratano, Antonino
Abstract: Aconitine intoxication by ingestion of Aconitum roots can lead to ventricular tachycardia and cardiac arrest and provides an example of the potential effect of self‐medication. Educational campaigns should be implemented to contain acute intoxications caused by herbal‐derived products. Abstract : Aconitine intoxication by ingestion of Aconitum roots can lead to ventricular tachycardia and cardiac arrest and provides an example of the potential effect of self‐medication. Educational campaigns should be implemented to contain acute intoxications caused by herbal‐derived products.